2020
DOI: 10.1080/01416200.2020.1734916
|View full text |Cite
|
Sign up to set email alerts
|

Argumentation in religious education in England: an analysis of locally agreed syllabuses

Abstract: The importance of developing students' ability to argue effectively is generally recognised across the curriculum, however what this means within religious education has not been thoroughly investigated. We explore this issue first through an initial review of both wider philosophical and curriculum literature on argumentation, notably Toulmin's work, and then a review of relevant research within religious education. We then describe our curriculum analysis, addressing three research questions focusing on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…The work of our research team has elsewhere reported a prominent presence of argumentation-related concepts within RE curriculum documents in England (Chan et al 2020). Insofar as argumentation can be considered the process of engaging with arguments or argument construction, it is evident that RE syllabi in England generally appear to include argumentation as a core skill.…”
Section: Argumentation In Religious Educationmentioning
confidence: 86%
See 1 more Smart Citation
“…The work of our research team has elsewhere reported a prominent presence of argumentation-related concepts within RE curriculum documents in England (Chan et al 2020). Insofar as argumentation can be considered the process of engaging with arguments or argument construction, it is evident that RE syllabi in England generally appear to include argumentation as a core skill.…”
Section: Argumentation In Religious Educationmentioning
confidence: 86%
“…Within the national science curriculum in England, argumentation is related to the 'Working Scientifically' component, particularly to 'development of scientific thinking' and 'analysis and evaluation' (DfE, 2014). Argumentation is also a component of the various regional RE syllabi in England (LCC 2016) where it is explicitly indicated as a learning outcome, although as mentioned earlier, the use of the word 'argument' is more prevalent in the RE syllabi (Chan et al 2020). Hence, argumentation is either implicitly and explicitly promoted in the curricula, and in this sense, the teachers from both subjects would have had the incentive to participate in the project.…”
Section: Context Of the Studymentioning
confidence: 99%
“…In prior research on science and RE teachers' views about the nature of argumentation in these two subjects, differences in the nature and range of acceptable evidence were highlighted Park 2020, 2021). As RE is itself a multidisciplinary subject, there are arguably no clear standards about what counts as evidence for an argument in the subject, or how different evidence is warranted (Chan, Fancourt, and Guilfoyle 2020). This possibility of operating with ill-defined argumentation standards of RE is also indicated in the performances of students in terms of warrants, where the RE performance was again lower than the other two contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the case of science education, argumentation has been less extensively researched in the context of religious education. However, argumentation is a strong feature of many Religious Education curriculum documents in England as students are asked to analyse and evaluate various truth claims about faith and various moral positions, and to generate well-informed and reasoned responses for themselves that draw on a range of sources (Chan, Fancourt, and Guilfoyle 2020). This form of religious education is often intended to contribute to pupils' understanding of and ability to contribute to issues of societal concern -thereby overlapping with SSI.…”
Section: Argumentation In the Disciplinesmentioning
confidence: 99%
“…These two strands are both subject-specific and cross-curricular, so their inter-relationship is often complex. We explore this across science and religious education, drawing on data from a wider research project, the Oxford Argumentation in Religious and Science education project ('OARS') (Erduran et al, 2019;Chan et al, 2020;Erduran, 2020;Guilfoyle et al, 2020;Guilfoyle, Hillier & Fancourt 2021). Science and religion can be seen as antithetical (e.g., Dawkins, 2006), and some argue that this also applies educationally (Mahner & Bunge, 1996).…”
Section: Introductionmentioning
confidence: 99%